Dehydration affects drug transport over nasal mucosa. (1st January 2019) - Ali, Abdullah; Wahlgren, Marie; Rembratt-Svensson, Birgitta; Daftani, Ameena; Falkman, Peter; Wollmer, Per; Engblom, Johan
Abstract: Formulations for nasal drug delivery often rely on water sorption to adhere to the mucosa, which also causes a higher water gradient over the tissue and subsequent dehydration. The primary aim of this study was therefore to evaluate mucosal response to dehydration and resolve the hypothesis that mucoadhesion achieved through water sorption could also be a constraint for drug absorption via the nasal route. The effect of altering water activity of the vehicle on Xylometazoline HCl and 51 Cr-EDTA uptake was studied separately ex vivo using flow through diffusion cells and excised porcine mucosa. We have shown that a modest increase in the water gradient over mucosa induces a substantial decrease in drug uptake for both Xylometazoline HCl and 51 Cr-EDTA. A similar result was obtained when comparing two different vehicles on the market; Nasoferm ® (Nordic Drugs, Sweden) and BLOX4 ® (Bioglan, Sweden). Mucoadhesion based on water sorption can slow down drug uptake in the nasal cavity. However, a clinical study is required to determine whether prolonged duration of the vehicle in situ or preventing dehydration of the mucosa is the most important factor for improving bioavailability.